The Changes in Intraocular Pressure and Central Corneal Thickness in The First 24 Hours of Life of Full-term Newborns - Dilber Çelik Yaprak; Işıl Kutlutürk Karagöz; Ahmet Elbay; Bilge Tanyeri Bayraktar; Gökhan Kılıç (Southern Clinics of Istanbul Eurasia, 2019)
INTRODUCTION[|]To evaluate to changes and the reasons of the changes in intraocular pressure (IOP) and central corneal thickness (CCT) in the first 24 hours of life of full-term newborns.[¤]METHODS[|]IOP,CCT measurements were determined by using Tono-Pen XL tonometer,portable pachymeter.In this prospective study we evaluate IOP and CCT of the 32right eyes of 32 newborn infants by vaginal delivery.The data was included.IOP and CCTmeasurements taken at 5th minutes just after the delivery and 24th h of the first day of the post partum period.Infant weights,heights,gender APGAR scores and gestational ages were also obtained.[¤]RESULTS[|]The mean IOP and CCT of right eyes was decreased significantly from18.67 +- 3.28 mmHg and684.72 +- 58.79 µm at the fifth minute after delivery to16.10 +- 2.87 mmHg and 611.28 +- 49.41 µm at the 24th hour of the postpartum period(p < 0.0001).There was no statistically difference between right-left eyes in terms of IOP and CCT at any measurement point. [¤]DISCUSSION AND CONCLUSION[|]We found that the mean IOP and CCT was decreased significantly between the values at the fifth minute after delivery and the 24th hour of the postpartum period.There is a need for more research to investigate the changes and the causes in IOP and CCT of newborns.[¤]